2019
DOI: 10.3390/ijerph16112003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regular Aerobic Exercise and Resistance Training on High-Density Lipoprotein Cholesterol Levels in Taiwanese Adults

Abstract: Increased levels of high-density lipoprotein cholesterol (HDL-C) can improve endothelial function. This may help reduce cardiovascular risks and mortality. Evidence has been provided on the association between cardiometabolic traits, such as HDL-C and exercise modalities. However, there is the absence of studies investigating this association in Taiwan. We assessed the relationship between exercise type and HDL-C among Taiwanese adults. Data were collected from Taiwan Biobank (TWB), a national biomedical resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…Regular exercise increases the level of HDL-C in a dose-response manner [ 5 8 ]. Almost all studies indicated that exercise increases HDL-C to some degree, which is a consistent result from both human [ 4 , 9 13 ] and rats [ 14 16 ]. Moreover, regular exercise was found to improve “cholesterol efflux capacity”, the ability of HDL-C to carry cholesterol from one’s bloodstream to the liver for clearance [ 17 ].…”
Section: Introductionmentioning
confidence: 74%
“…Regular exercise increases the level of HDL-C in a dose-response manner [ 5 8 ]. Almost all studies indicated that exercise increases HDL-C to some degree, which is a consistent result from both human [ 4 , 9 13 ] and rats [ 14 16 ]. Moreover, regular exercise was found to improve “cholesterol efflux capacity”, the ability of HDL-C to carry cholesterol from one’s bloodstream to the liver for clearance [ 17 ].…”
Section: Introductionmentioning
confidence: 74%
“…The same study showed a prevalence of T2D significantly decreasing across the CRF quartiles (from 7.0% to 0.9% in men and 5.8% to 0.4% in women), which was also observed in Brazilian subjects (20–59 years) (22.9% versus 0.9% in men and 12.2% versus 1.8% in women) [ 30 ]. The association between CRF and dyslipidemia is very well documented [ 44 , 45 , 46 ]. In fact, there are non-exercise models that include dyslipidemia as an independent variable [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is why it is essential that much evidence supports the role that RT improves HDL-cholesterol whilst reducing total cholesterol, LDL-cholesterol and triglycerides in adults [41][42][43]. What is particularly interesting is that RT shows a stronger association than aerobic exercise when attempting to improve HDL-cholesterol [44,45]. It appears that an increased volume (via increased numbers of sets or repetitions), rather than intensity or load, has a greater impact on lipid profiles [46].…”
Section: Resistance Training and Prevention And Management Of Cardiovascular Disease (Cvd)mentioning
confidence: 99%